Testicular tunica vaginalis grafting for the treatment of Peyronie’s disease: a case report - Rahmat Husein; Antono Pratanu (Intisari Sains Medis, 2020)
Introduction: Peyronie’s disease (PD) is a progressive fibrotic tissue disorder of the penile tunica albuginea. PD can cause the formation of fibrous plaques, penile deformity, pain during erection, penile curvature, and erectile dysfunction (ED). Surgical treatment is the gold standard in PD because it is a fast and reliable therapy. There are many surgical options for PD such as plication procedures, incision and grafting procedures, and implantation of penile prosthesis. There are three types of graft material have been reported: autologous graft, xenograft and synthetic graft. Considering the higher rate of infections, inflammatory reactions and allergies, synthetic grafts are rarely used. Autologous graft is currently widely used because of the incidence of inflammatory reactions and low allergic reactions. Tunica vaginalis grafts are rarely used widely. Testicular tunica vaginalis was first reported as an autologous graft in 1980.Case Report: A 53-year-old man comes to the urology clinic at Sidowaras Hospital complaining of pain during erection and erection cannot be straight. This complaint has been felt since a few months ago but the patient ignored it. An assessment of ED with International Index of Erectile Function (IIEF)-5 score obtained a score of 12 (mild-moderate dysfunction). Physical examination found a curvature of the penis around 700 and in palpation there was a hard lump on the dorsal penis. After the diagnosis was made, testicular tunica vaginalis grafting procedure was performed on this patient. At a 6-month re-evaluation after surgery, patient-reported reduced penile pain on erection with improved erectile function score (IIEF)-5 score 21 (mild dysfunction).Conclusion: Testicular tunica vaginalis grafting was chosen because it is feasible and safe for patient with PD. Testicular tunica vaginalis Grafting used due to their easy incorporation into host tissue and few incidences of local inflammatory reaction.